The Evolution of Platform Science - Mirowski, Philip (Social research, 2023)
Although we have been living through an era of the commercialization of science since the 1980s, something has dramatically changed over the last decade. Whereas commercialization used to subject research outputs to market considerations, a new development seeks to monetize nearly all aspects of the research process. This has become manifest under the rubric of “open science” as the purported solution to what is perceived to ail modern science. The commercial interests behind top journal publishers are pursuing control over “open science” by imposing the structures of “platform capitalism” upon the research process. The release of ChatGPT is best understood as the latest act in this drama, with Silicon Valley AI platforms threatening to displace the Big Five publishers as the primary protagonists of the commercialization of science.